2020
DOI: 10.3390/jcm9041005
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Comorbidities in Patients with De-Novo Diffuse Large B-Cell Lymphoma Treated with R-CHOP Immunochemotherapy in Curative Intent

Abstract: Background: Patient-related factors, namely comorbidities, impact the clinical outcome of patients with diffuse large B-cell lymphoma (DLBCL). Methods: The prevalence and prognostic impact of comorbidities were examined using the validated scores Charlson Comorbidity Index (CCI) and Hematopoietic Cell Transplantation-specific Comorbidity Index (HCT-CI) in 181 patients with DLBCL at initial diagnosis before treatment with rituximab, cyclophosphamide, vincristine, doxorubicin and prednisone (R-CHOP). Results: Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This study has revealed important results in terms of demonstrating the effectiveness of CCI in our own patient population. In the study conducted by Kocher et al in 2020 [14], the effectiveness of CCI and Hematopoietic Cell Transplantation Specific Comorbidity Index (HCT-CI) were examined in 181 patients with DLBCL. All patients received R-CHOP, and a higher CCI score was associated with a lower rate of complete response (p = 0.020).…”
Section: Discussionmentioning
confidence: 99%
“…This study has revealed important results in terms of demonstrating the effectiveness of CCI in our own patient population. In the study conducted by Kocher et al in 2020 [14], the effectiveness of CCI and Hematopoietic Cell Transplantation Specific Comorbidity Index (HCT-CI) were examined in 181 patients with DLBCL. All patients received R-CHOP, and a higher CCI score was associated with a lower rate of complete response (p = 0.020).…”
Section: Discussionmentioning
confidence: 99%
“…In DLBCL, CCI scores above 2 were shown to be associated with a significantly higher mortality [14]. Among first-line patients receiving R-CHOP regimen, 3-year survival rate was 39% for those with a CCI score C 2 while the respective value for patients with a CCI of 0 or 1 was twice as high (81%) [15].…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
“…Indeed, while the elder age has been traditionally considered an independent poor prognostic factor in various prognostic indices for DLBCL, such as the revised International Prognostic Index (R‐IPI), the National Comprehensive Cancer Network International Prognostic Index (NCCN‐IPI), and the Kyoto Prognostic index (KPI), 5–7 the global geriatrification of society has brought substantial changes in the overall landscape of daily practice for DLBCL. Currently, more than 30% of DLBCL patients are older than 75 years at their disease onset, 1 and factors other than treatment response, such as lymphoma‐unrelated comorbidities and a high frequency of adverse events leading to intolerance to treatment, have significant prognostic impacts in elderly patients with DLBCL 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, more than 30% of DLBCL patients are older than 75 years at their disease onset, 1 and factors other than treatment response, such as lymphoma-unrelated comorbidities and a high frequency of adverse events leading to intolerance to treatment, have significant prognostic impacts in elderly patients with DLBCL. [8][9][10][11] Sarcopenia is the depletion of skeletal muscle mass and muscle strength and is closely associated with aging and frailty. 12 Also, sarcopenia is biologically linked with the dysregulation of inflammatory cytokines and adipokines.…”
Section: Introductionmentioning
confidence: 99%